การระบายอากาศโดยวิธีทางธรรมชาติ : แนวทางการออกแบบปรับปรุงผังอาคารชุดพักอาศัย กรณีศึกษาโครงการบ้านเอื้ออาทร - สริน พินิจ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The present research aimed at investigating the effectiveness of the planning design of residential buildings with natural ventilation in Thailand. The Eur Ar Thorn Housing Project was selected as a case study. As the study focused on the feasibility of natural ventilation to replace thermal comfort and to reduce hours of air-conditioning system use, the computational fluid dynamics (CFD) program was used with the sample building to assess the efficiency of ventilation and to propose guidelines on improvement of design. The improvement of the buildings can be divided into two main methods. The first method was the improvement of the existing plans by adding air trapping equipment, increasing the number of openings between the bedroom and the living room, and expanding the shared walkways. The second method is the adjustment of the building plans by increasing the empty space between residential units, using a single-walkway plan, and reducing the number of units on each floor. The research findings revealed that residential buildings in Thailand can utilize natural ventilation to create comfort. It was also found that increasing the empty space between residential units can best increase ventilating efficiency, followed by increasing the number of openings between the bedroom and the living room in all units. The guideline for improvement of building plans that was least effective for ventilation was making the shape of a building square by reducing the number of units to four units on each floor. This means that to design floor plans to ensure sufficient natural ventilation, if the unit is small, dividing the unit into several small bedrooms should be avoided as it adversely affects ventilation in the rooms. In addition, designing a floor plan as an elongated rectangle can considerably help increase wind speed in each room. The findings of the present study have yielded guidelines on design of residential buildings in Thailand to maximize natural ventilation efficiency.